Review on Chuntaivatral Chooranam In Siddha Medicine - Miraaj, R.; Subramanieam, N. (Gampaha Wickramarachchi University of Indigenous medicine yakkala, Sri Lanka, 2025)
Chuntaivatral Chooranam is a polyherbal preparation used to treat various diseases, such as diarrhea, dysentery, indigestion, and haemorrhoids. It is mentioned in siddha vaitya Thirattu and contains 7 ingredients. This review study is focused on developing scientific documentary evidence for the medicinal ingredients of Chuntaivatral Chooranam. This study presents an organized compilation and analysis of data sourced from traditional Siddha Medicine textbooks and research publications on the website. The data, drawn from a variety of ancient and contemporary texts, were systematically collected and categorized from October to November 2024. The collected data were processed and analysed using MS Excel spreadsheets. ALL ingredients of Chuntaivatral Chooranam are herbs from seven different families. According to the data, the parts used in the plants are seven different sources: dried fruit, leaf, dried pericarp, kernel, fruit and seed; each represents 14.28%. Out of 7 ingredients, 42.85% have an astringent taste, 57.14% have cold potency, and 85.71% have pungent efficacy. Based on phytochemical analysis of the ingredients, 100% of the ingredients constitute flavonoids, tannin, phenol, saponin, volatile oil, alkaloid, and ascorbic acid, while 42.85% of them are carbohydrates and protein (42.85%). All the ingredients show astringent, antimicrobial and antioxidant activity; 85.71% exhibit antidiarrheal, while 57.14% each show stomachic, anthelmintic and antidiabetic activity. Therefore, this review provides useful documentation of Chuntaivatral Chooranam. However, further scientific studies regarding chemical and toxicity analysis should be performed in the future.
Keywords: Chuntaivatral Chooranam; Siddha medicine; Astringent; Polyherbal; Indigestion; Tannin